2020
DOI: 10.1108/ijbpa-05-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of passive design strategies to achieve NZEB in the corporate facilities: the context of Bangladeshi subtropical monsoon climate

Abstract: PurposeThis study investigates the impact and economic viability of energy-efficient building envelope and orientation for contributing net zero energy building (NZEB) and suggests optimum thermal insulation thickness, optimum wall thickness, appropriate orientation and glazing types of window in the contexts of unique Bangladeshi subtropical monsoon climate.Design/methodology/approachThe whole study was conducted through energy simulation perspective of an existing office building using building information m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The authors concluded that the workflow is effective, however, adaptations to the model were necessary before the simulation. Rana et al [24] analyze passive strategies for energy efficiency with BIM/BES workflow through the modeling of office buildings in Khulna, Bangladesh using Revit 2017 and comparisons between two BES software, eQUEST and GBS. It was concluded that the two BES software's presented similar results because they have DOE-2 as a simulation mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors concluded that the workflow is effective, however, adaptations to the model were necessary before the simulation. Rana et al [24] analyze passive strategies for energy efficiency with BIM/BES workflow through the modeling of office buildings in Khulna, Bangladesh using Revit 2017 and comparisons between two BES software, eQUEST and GBS. It was concluded that the two BES software's presented similar results because they have DOE-2 as a simulation mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be said that energy efficiency is the first objective of NZEB development, followed by the production of renewable energy from on-site or off-site sources, requirements that cannot be minimized; therefore, to achieve renewable energy technologies such as photovoltaics, wind turbines, solar thermal, district heating, heat pumps, and cooling must be mounted to meet the lasting energy requirements. Likewise, the energy-efficient building envelope is composed of wall thickness, thermal insulation materials, appropriate glazing type, and insulation thickness, which can provide energy efficiency by reducing solar heat increase and cooling load in the subtropical climate in terms of direct solar heat increase, and daylight implementation can be optimized by proper position [24,25].…”
Section: Energy Measures According To Building Type and Climatementioning
confidence: 99%
“…In tropical/subtropical climates, a lot of energy is consumed for refrigeration, and conventional air conditioners are widely used [24]; envelope systems for buildings in hot and humid climates are the main shield to reduce cooling loads for NZEBs. Those characteristics of the envelopes shared by NZEBs can be summarized in the following parameters [1]:…”
Section: Envelope For Active Coolingmentioning
confidence: 99%
“…In this case, the consumption for an identical building, taking into account the Internal Partitions adopts the value of 91.875 kWh/m 2 year (Equation ( 4)) with a result of the simulation equal to 92. 23…”
Section: Application Examplesmentioning
confidence: 99%